Factors affecting attitudes towards caring for terminally ill patients among nursing students in Switzerland: a cross-sectional study - Jérôme Pasquier; Pauline Laporte; Typhaine Juvet; Jean-François Desbiens; Diane Tapp; Marc-Antoine Bornet (BMJ Open)
Objectives Positive attitudes towards end-of-life care are essential among nursing students to adequately support terminally ill patients and enable students to feel confident about providing end-of-life care. This study aimed to determine nursing students’ attitudes towards caring for terminally ill patients, as well as the associations between these attitudes and year of study, exposure to terminally ill people, self-perceived nursing skills and subjective impact of instruction.Design Cross-sectional study.Setting A health sciences school in Switzerland.Participants All preparatory students, first-year nursing students and third-year nursing students were invited to participate; 178 agreed to participate.Primary outcome measure Attitudes towards terminally ill patients were assessed using the Frommelt Attitudes Toward Care of the Dying Scale, Form B (FATCOD, Form B), as the primary outcome. Secondary measures were gender, age, year of study, number of terminally ill persons encountered, self-perceived palliative care nursing skills and subjective impact of instruction.Results Mean FATCOD, Form B score was 117.7 (SD: 9.8, median: 118.0). Better attitudes towards terminally ill patients were significantly associated with being aged 24–26 years (β=6.97, 95% CI 2.00 to 11.95, p=0.006), year of study (β=3.47, 95% CI 1.69 to 5.25, p<0.001), professional encounters with terminally ill patients (β=3.59, 95% CI 2.23 to 4.95, p<0.001) and self-perceived palliative care nursing competence (β=1.23, 95% CI 0.41 to 2.04; p=0.003). In the multivariate analysis, professionally encountering terminally ill patients remained significant (β=3.00; 95% CI 1.43 to 4.57; p<0.001).Conclusions Nursing students’ attitudes towards caring for terminally ill patients were positive and improved as their year of study progressed. Professional exposure to terminally ill patients was the strongest factor, followed by private encounters, self-perceived palliative care nursing skills, year of study and age.